Acute safety and 30-day outcome after percutaneous edge-to-edge repair of mitral regurgitation in very high-risk patients - Pleger, Sven Torsten; Mereles, Derliz; Schulz-Schönhagen, Marius; Krumsdorf, Ulrike; Chorianopoulos, Emmanuel; Rottbauer, Wolfgang; Katus, Hugo; Bekeredjian, Raffi (The American journal of cardiology, 2011)
Percutaneous edge-to-edge mitral valve repair using the MitraClip device has evolved as a new tool for the treatment of severe mitral valve regurgitation. This technique has been evaluated in surgical low- and high-risk patients. Patients with advanced age, multiple morbidities, and heart failure will be the first to be considered for a nonsurgical approach. Thus safety and feasibility data in very high-risk patients are crucial for clinical decision making. The aim of this study was to assess short-term safety and clinical efficacy in high-risk patients with a Society of Thoracic Surgeons (STS) score >15% after MitraClip implantation (mean STS score 24 ± 4%). All relevant complications, mortality, echocardiographic improvement, and changes in brain natriuretic peptide, high-sensitive troponin T, 6-minute walk distance test, and New York Heart Association functional class were collected in patients within 30 days after MitraClip implantation. Mitral regurgitation had significantly decreased after 30 days from grade 2.9 ± 0.2 to 1.7 ± 0.7 (p < 0.0001). Accordingly, New York Heart Association functional class had significantly improved from 3.38 ± 0.59 to 2.2 ± 0.4 (p <0.001). Objective parameters of clinical improvement showed a significant increase in 6-minute walk distance test (from 194 ± 44 to 300 ± 70 m, p <0.01) and insignificant trends in brain natriuretic peptide (10,376 ± 1,996 vs 4,385 ± 1,266 ng/L, p = 0.06) and high-sensitive troponin T (43 ± 8.9 vs 36 ± 7.7 pg/L, p = 0.27) improvement. Thirty-day mortality was 0. Two patients developed a left atrial thrombus, 1 patient was on a ventilator for >12 hours, and 1 patient had significant access site bleeding. In conclusion, this study shows that percutaneous edge-to-edge mitral valve repair can be safely performed even in surgical high-risk patients with an STS score >15. At 1-month follow-up most patients showed persistent improvement in mitral regurgitation and a clinical benefit.
Gesehen am 21.12.2022